List of Trade Unionists & Labour Party Members [International Brigade]
1937 034-0192-011 9. L. Herbert Nat. Union Com. Travelers Central Br. Dependant: R. Hilliard NUJ Central London Br. Dependant: T. Killich NUC M/c. General No.1 J. Kelley United Ladies Tailoring London West Dependant: G. Leat Bakers and Allied Trades Glasgow East End Br. Dependant: Mrs.G. Leat, 8 Rewchester St., Glasgow S.E. (£2-0-0.) J. Lees Piecers Union, Rock St. Br. Oldham. Dependant: Mrs. Lees, 15 Snowden St., Oldham (15/-) J. May Ship and Painters Union Bristol Dependant: J. Mooney Nat Assoc. Theatrical Employees Dependant: R. O'Neill Typ. Assoc. Chapel Steward Belfast. Dependant: J. Rawlings NUFW Birkenhead Br. Cte. Br. Referee T.C.Del. Dependant: Mrs. J. Rawlings. 18 Ivydale Rd., Birkenhead. (£2-0-0). K. Stalker Ass. Eng.& Shipbldrs. Draughtsmen Cen. London Br. Dependant: E. Starr AUU Manchester 2. Dependant: J. Sylvester NUT London Teaching Asso. Dependant: C. Walstencroft, Piecers Union Rock St. Br. Oldham. Dependant: ADDENDUM *T. Anderson TGWU 7/13 also Sec. St. Rollox (Glasgow) DLP. Dependant: Mrs. Anderson, 38 St. Calir St., Glasgow N.W. (£1-10-0) H. Boddy NUS Cardiff Dependant: P. Curley Boilermakers Bowling No.1 Clyde Dist. Shopt Steward. Dependant: Mrs. Curley, 29 Union St., Benhall, Dumbartonshire. (£1-0-0) 292/946/34/193(ix)